Life on the Grid: 100 Years of Street Photography in Toronto. CITY OF TORONTO ARCHIVES. - Roussain, James (Archivaria, 2014)
Life on the Grid: 100 Years of Street Photography in Toronto. CITY OF TORONTO ARCHIVES. Curated by PATRICK CUMMINS. Mounted at the City of Toronto Archives, Toronto, 27 June 2013–May 2014.